Recommendations for removing access barriers to effective Sexual/Reproductive Health Services (SRHS) for young people in South East Nigeria: A systematic review - Benjamin O Ajibade; Chika Oguguo; Jonathan Ling; Judith Eberhardt (International Journal of Sexual and Reproductive Health Care - Peertechz Publications, 2022)
Young people's Sexual and Reproductive Health (SRH) services in Nigeria are limited and there are issues of affordability and accessibility of these health services. Also, there are limited studies in Nigeria on the barriers to accessing and utilizing SRHS in the Nigerian healthcare sector. Furthermore, even when the services are provided they are not sensitive to the needs of young people. Hence, this study aims to assess the barriers to the availability and accessibility of sexual reproductive health services (SRHS) for young people living with sexually transmitted infections (STIs) in Abia State, Nigeria. Study Aim: To make recommendations for removing assess barriers to effective sexual and reproductive health services for young people living with STIs in southeast Nigeria. Methodology: A systematic review of 14 studies comprising 9 qualitative studies, 3 mixed methods, 1 quantitative and 1 cross-sectional study. The inclusion criteria were primary studies written in the English language which assessed barriers to SRH services while the exclusion criteria were the secondary studies and primary studies which did not access barriers to accessibility and availability of SRHS for young people. A total of 4, 705 participants from different African countries formed the sample size. Findings: Results showed that young people have little or no insight into STIs and their services. Moreover, they experienced different levels of barriers ranging from the negative and judgmental attitude of healthcare providers, stigma, cost, availability and accessibility of healthcare services as well as lack of integration of services and privacy and confidentiality. These are the major barriers that discourage young people from accessing SRH services. Also, experiences of fear and shame were reported as common barriers to utilizing care.  Conclusion: Sensitizing the SRH needs of young people can enhance access to healthcare services. Therefore, there is a need to improve uptake and address the negative attitude of healthcare providers, as well as the issue of confidentiality, which will help to improve SRH service utilization among young people. Also, it is recommended that teaching health care professionals about these STI prevention centers will be the main solution to improve the preventive practice to reduce STI incidence in young people in Nigeria.